Blue Nile (Abay) hydropower potential, prioritization and tradeoffs on priority investments - Desalegn, D.T.; Awulachew, Seleshi Bekele; Moges, S. A. (2008)
Ethiopia is among countries which has very low modern energy sources. The topographic feature and the available water of Ethiopia permit to have a large hydropower potential. However, as the available runoff in rivers has very high hydrological variability, tapping in to this potential require investment on storage to smooth the temporal hydrological variability. In this paper, first the behaviour of this hydrological variability and implication of water resources development is discussed. Secondly, various documents and reports provide varying values of hydropower potential of Ethiopia and Abbay. To close the information gap, topographical and hydrological site evaluation for the selected hydropower potential sites have been carried out, for 129 possible potentials sites which are identified by WAPCOS in 1990 and having total capacity of 13,845 MW. After evaluations these sites 91 possible sites with potential of 12,148 MW are identified and mapped under various sub-basins. Dabus sub-basin stands first among the 16 sub-basins by 13 hydropower potential sites and these sites give 3524MW. In order to exploit the available hydropower potential in the country, it is crucial to rank these sites. The ranking of these sites have been carried out based on cost per kilowatt hour of the hydropower potential (HP) sites. Furthermore, the paper discusses the benefits and tradeoffs for four priority development identified by ENTRO as Eastern Nile fast track projects.